Effects of geometric factors and shear band patterns on notch sensitivity in bulk metallic glasses. (December 2016) - Li, Weidong; Bei, Hongbin; Gao, Yanfei
Abstract: Recent experiments in notched bulk metallic glasses have found reduced, or insensitive, or improved strengths, while in many of these cases the ductile strain prior to final failure is enhanced. First, although the inverse notch effect is explained by a shift from shear localization to cavitation failure, it is suggested in this work that the synergistic effect between cohesive fracture at the notched area and shear bands emanating from the notch roots may extend the parametric space for the notch insensitive behavior. Second, the dependence of shear band patterns on notch geometric factors is determined by the Rudnicki-Rice theory and the free-volume-based finite element simulations. These results suggest conditions for shear band multiplication to take place and for the shear-localization-induced failure to be delayed. Highlights: Notched bulk metallic glasses may have reduced, or insensitive, or improved strengths. Shear bands emanating from the notch roots may delay the cohesive fracture at the notched area. Shear band multiplication may be realized by tuning the notch geometric factors.